2002
DOI: 10.1067/mtc.2002.121285
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery with deep hypothermic circulatory arrest produces less systemic inflammatory response than low-flow cardiopulmonary bypass in newborns

Abstract: Deep hypothermic circulatory arrest produces less systemic inflammatory response than low-flow cardiopulmonary bypass. In addition, there is an indication of less fluid accumulation postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…This finding may be explained by a reduced incidence of systemic inflammatory response syndrome provoked by DHCA. 18,19 Other intraoperative factors, such as longer cardiopulmonary bypass time, 20 and extracardiac Fontan procedure, 21 have been associated with longer LOS in other studies, whereas fenestration and use of modified ultrafiltration have been found to be associated with shorter LOS. 15 In our study, none of these factors predicted LOS; and no pre–Fontan procedure catheterization variables or catheter-based interventions were associated with LOS.…”
Section: Discussionmentioning
confidence: 87%
“…This finding may be explained by a reduced incidence of systemic inflammatory response syndrome provoked by DHCA. 18,19 Other intraoperative factors, such as longer cardiopulmonary bypass time, 20 and extracardiac Fontan procedure, 21 have been associated with longer LOS in other studies, whereas fenestration and use of modified ultrafiltration have been found to be associated with shorter LOS. 15 In our study, none of these factors predicted LOS; and no pre–Fontan procedure catheterization variables or catheter-based interventions were associated with LOS.…”
Section: Discussionmentioning
confidence: 87%
“…Additional variables that may have an important impact on the inflammatory response to CPB were not addressed in this study. For example, the use of deep hypothermic circulatory arrest rather than low-flow CPB appears to have favorable clinical effects on the postoperative inflammatory response in infants (27,28). Future prospective studies of steroid use during CPB should be designed to limit the potential confounding effects of such variables.…”
Section: Discussionmentioning
confidence: 95%
“…In this surgical setting, body temperatures of neonates are typically reduced to Յ18°C, a temperature that optimizes reductions in several pro-inflammatory markers (plasma IL-8, IL-6, anaphylatoxin C3a, and body weight gain; Ref. 35). In an experimental model of cardiopulmonary bypass in pigs, hypothermia was associated with reductions in lung tissue damage and plasma TNF-␣ and an increase in plasma IL-10 expression (15).…”
Section: Discussionmentioning
confidence: 99%